Avoiding emissions versus creating sinks—Effectiveness and attractiveness to climate finance. Issue 8 (26th January 2023) - Williams, Mathew; Reay, Dave; Smith, Pete
Abstract : The perception of greater impact via new sinks, as opposed to through avoided emissions, has already led some large investors to focus on sink‐related projects. This is a flawed perception when applied universally and carries a risk that effective routes to mitigation through avoiding emissions are side‐lined. In reality, both emissions avoidance and emissions removal are needed, and both can be a cost‐effective means of delivering mitigation.